HUBUNGAN GANGGUAN GINJAL DENGAN ANGKA KEMATIAN PADA PASIEN RAWAT INAP COVID-19 DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG - Gerizha, M. Rakha; Yonata, Ade (Medula, 2026)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The risk of death from Covid-19 is reported to be higher due to kidney damage which causes various complications in patients. The background of this research was to determine the relationship between kidney disorders and the mortality rate of inpatients with Covid-19 at RSUD Dr. H. Abdul Moeloek, Lampung. This type of research is a retrospective analytic descriptive with a cross sectional approach, conducted from November to December 2022 at the Abdul Moeloek Hospital in Bandar Lampung. The population in this study were patients diagnosed with Covid-19 who were recorded as inpatients at RSUD Dr. H. Abdul Moeloek with a total of 361 samples selected according to the inclusion and exclusion criteria. The analytical test in this study used the Chi square test. Based on research, the majority of Covid-19 patients were female, aged 19- 59 years, with length of stay <14 days. The mortality rate for Covid-19 patients with comorbid kidney disorders is 54%. The results of the Chi Square test for the relationship between kidney impairment and mortality in Covid-19 hospitalized patients showed a p-value of 0.000. There is a relationship between kidney disorders and the death rate of Covid-19 inpatients at Dr. H. Abdul Moeloek Lampung Province. Hospitalized patients with comorbid CKD are more at risk of dying compared to Covid-19 patients without CKD.